MANAGEMENT OF MONTESSORI-BASED ARABIC CURRICULUM DEVELOPMENT IN PRE-SCHOOL STUDENTS - Uswatul Jannah -; Umar Faruq; Moh. Zainol Kamal (Lembaga PInstitut Kariman Wirayudha Sumenep Madura, 2025)
Abstract: This research aims to analyze the management of Montessori-based Arabic curriculum development for pre-school students at Raudlatul Athfal An-Nidham Sumenep. This research uses a qualitative approach with a case study type. Data were collected through observation, interviews and documentation. The results showed that the implementation of Montessori-based Arabic curriculum at RA An-Nidham involves careful planning, implementation in accordance with Montessori principles, and continuous evaluation. This research contributes to the development of Montessori-based curriculum in the context of Arabic language education at the early childhood education level. Keyword: Curriculum Management, Montessori, Pre-school Arabic